FUNCTIONAL STYLES IN ENGLISH LANGUAGE AND UZBEK LANGUAGE: A COMPARATIVE ANALYSIS - Qo’ziyeva Mubinaxon No’monjon qizi (TADQIQOTLAR, 2026)
Abstract: This article examines the system of functional styles in the English and Uzbek languages, highlighting their similarities and differences. Functional styles reflect how language varies depending on communicative purpose, social context, and audience. The study focuses on five major styles in both languages: scientific, official, publicistic, literary, and colloquial. Through comparative analysis, the article identifies both universal and language- specific features shaped by cultural and linguistic traditions.The views of I.R. Galperin and I.V. Arnold on the classification of functional styles are outlined and compared. The article also presents the main characteristics of different styles and highlights their importance for effective communication.